Effects of methylphenidate in children with attention deficit hyperactivity disorder: a near-infrared spectroscopy study with CANTAB® - Matsuura, Naomi (Child Adolesc Psychiatry Ment Health, 2014)
BACKGROUND: A wide range of evidence supports the methylphenidate (MPH)-induced enhancement of prefrontal cortex (PFC) functioning and improvements in behavioral symptoms in patients with attention deficit hyperactivity disorder (ADHD). Although working memory (WM) has been hypothesized to be impaired in patients with ADHD, no pharmacological studies have examined visuospatial WM (VSWM) with near-infrared spectroscopy (NIRS). STUDY AIM: The present study was designed to investigate the acute effects of MPH on neuropsychological performance and hemodynamic activation in children with ADHD during VSWM tasks. METHODS: The subject group included 10 boys and 1 girl previously diagnosed with ADHD. Two VSWM tasks of differing degrees of difficulty were conducted. This is the first study on the pharmacological effects of MPH in children with ADHD to evaluate hemodynamic responses in the PFC with simultaneous NIRS. RESULTS: No significant differences were found in the scores for both spatial working memory (SWM) and score of spatial span (SSP) tasks between the MPH-off and MPH–on conditions. However, a significant MPH-effect on changes in oxy-hemoglobin levels in the PFC was found only in the SWM task. CONCLUSION: These findings suggest that PFC activation might be affected by MPH, depending on the degree of difficulty of the particular task. Although the MPH-induced change on behavior may or may not be obvious, NIRS measurements might be useful for assessing the psychological effects of MPH even when performance changes were not observed in the cognitive tasks.